THE EFFECTS OF 'PROFETAL' PREPARATION UPON FUNCTIONAL ACTIVITY OF HUMAN MONONUCLEAR LEUKOCYTES AND DENDRITIC CELLS - V. A. Chereshnev; O. V. Lebedinskaya; C. Yu. Rodionov; N. K. Ahmatova; I. Zh. Shubina; E. A. Lebedinskaya; T. V. Gavrilova; M. V. Kisselevsky (Медицинская иммунология, 2014)
Abstract. The effects of 'Profetal', a drug containing liophylized, dextran-stabilized human alpha-fetoprotein as main active component, were investigated on peripheral donor blood mononuclear leukocytes (ML), with respect to their functional properties and the potential to generate mature dendritic cells (DC). Addition of the drug to cell cultures at optimal doses was shown to cause significant increase in their proliferative capacity and ML blastic transformation levels, and enhanced cytotoxicity towards K562 tumor cells, as well as to induce maturation of antigen-presenting dendritic cells. On the basis of the data obtained, a conclusion is made that 'Profetal' is an active immunomodulatory factor, and it may be applied for generation of cytotoxic lymphocytes and mature DC, aiming to apply them for the biotherapy of oncological and infectious diseases.